Bacterial flora of the human oral cavity, and the upper and lower esophagus. Issue 1 (6th March 2012) - Norder Grusell, E.; Dahlén, G.; Ruth, M.; Ny, L.; Quiding‐Järbrink, M.; Bergquist, H.; Bove, M.
Summary This reference study aims to survey the bacterial flora of the healthy lower human esophagus and to compare it with that of the upper esophagus and oral mucosa. The use of biopsies, in addition to brush samples, allows inclusion of not only transient bacteria present on the surface but also bacteria residing in the epithelia, and the yield of the two methods can be compared. Forty patients scheduled for surgery for reasons with no known influence on esophageal flora and with no symptoms or endoscopic signs of esophageal disease were included. Samples were collected from the oral, upper esophageal, and lower esophageal mucosa using sealed brushes and biopsy forceps. Colonies cultivated on agar plates were classified and semiquantified. Twenty‐three different bacterial species were identified, with similar strains present at the three sites. The most common group of bacteria was viridans streptococci, with an occurrence rate in brush samples and biopsies of 98% and 95%, respectively. The median number of species occurring in the oral cavity, upper esophagus, and lower esophagus was between 3 and 4 (range 0–7). The total number of species in the oral cavity was significantly higher when compared with either level in the esophagus, while the yields obtained by brush and biopsy sampling were highly correlated. Hence, the normal human esophagus is colonized with a resident bacterial flora of its own, which has similarities to that of the oral mucosa. There are diverse species that make up this flora, although in relatively low amounts. The most frequent inhabitants of the esophagus are streptococci, with an occurrence rate in brush samples and biopsies of 95–98%. Comparative studies of patients with eosinophilic esophagitis and gastroesophageal reflux disease are warranted.